Financial Performance in Indonesian Companies: The Role of Environmental Performance and Environmental Disclosure - Lastiningsih, Noegrahini; Aswar, Khoirul; ., Ermawati (Journal of Economics and Behavioral Studies, 2020)
The aim of this study is to acquire empirical evidence that environmental performance and environmental disclosure has an influence on financial performance. The key differentiation between this study and previous studies is the use of different variables and measurement methods. The hypothesis of this study is based on stakeholder theory and legitimation theory. The purposive sampling method was used to collect data from manufacture companies listed in the Indonesian Stock Exchange and the PROPER 2016-2018 program. Instruments for classic assumptions have been tested. Afterwards, multiple linear regression is used as the analysis method, and secondary data types with the use of documentation methods. The outcome of this study shows that environmental performance and environmental disclosure has a significantly positive influence towards financial performance.